The Phonological Interference of Sasak Meno-Mene Dialect on English Pronunciation: A Case Study of Eleventh Grade Students at SMA Negeri 1 Janapria - Bahril, Bahril; Arafiq, Arafiq; Isnaeni, Muh; Mahyuni, Mahyuni (LITPAM, 2025)
This study employs a qualitative approach with a case study design to examine the phonological interference of the Sasak Meno-Mene dialect (L1) on English (L2) pronunciation among eleventh-grade students at SMA Negeri 1 Janapria. The primary objective is to identify phonological differences and determine recurring patterns of pronunciation errors. Data were collected from 75 native speakers of the Meno-Mene dialect through minimal-pair testing, observations, and semi-structured interviews. The analysis reveals that the phonological system of the first language, which is comparatively simpler, lacks several key English phonemes, such as interdental fricatives (/?/, /ð/) and vowel length distinctions. The findings indicate consistent negative transfer, predominantly in the substitution of interdental fricatives with alveolar stops (/?/ ? /t/). Furthermore, the substitution of /f/ with /p/ suggests that the labiodental fricative, although present in loanwords, has not yet been fully internalized by the learners. Non-linguistic factors also contribute to the learners’ difficulties, including language anxiety and fear of ridicule, which discourage students from practicing spoken English and limit opportunities for self-correction. This research supports the Contrastive Analysis Hypothesis (CAH) and recommends that pronunciation instruction be targeted and psychologically supportive in order to enhance learner performance.